Driver self-regulation and depressive symptoms in cataract patients awaiting surgery: a cross-sectional study - Fraser, Michelle; Meuleners, Lynn; Ng, J.; Morlet, N. (BioMed Central, 2013)
Background: Cataract is an extremely common visual condition of ageing. Evidence suggests that visual impairment influences driving patterns and self-regulatory behavior among older drivers. However, little is known about the psychological effects of driver self-regulation among older drivers. Therefore, this study aimed to describe driver self-regulation practices among older bilateral cataract patients and to determine the association between self-regulation and depressive symptoms. Methods: Ninety-nine older drivers with bilateral cataract were assessed the week before first eye cataract surgery. Driver self-regulation was measured via the Driving Habits Questionnaire. Depressive symptoms were assessed using the 20-item Center for Epidemiological Studies Depression Scale. Visual, demographic and cognitive data were also collected. Differences between self-regulators and non self-regulators were described and linear regression modeling used to determine the association between driver self-regulation and depressive symptoms score. Results: Among cataract patients, 48% reported self-regulating their driving to avoid at least one challenging situation. The situations most commonly avoided were driving at night (40%), on the freeway (12%), in the rain (9%) and parallel parking (8%). Self-regulators had significantly poorer contrast sensitivity in their worse eye than non self-regulators (p = 0.027). Driver self-regulation was significantly associated with increased depressive symptoms after controlling for potential confounding factors (p = 0.002).Conclusions: Driver self-regulation was associated with increased depressive symptoms among cataract patients. Further research should investigate this association among the general older population. Self-regulation programs aimed at older drivers may need to incorporate mental health elements to counteract unintended psychological effects.